Hindi LupusPRO: cross cultural validation of disease specific patient reported outcome measure of lupus. (November 2019) - Pinto, B; Jolly, M; Dhooria, A; Grover, S; Raj, J M; Devilliers, H; Sharma, A
Background: LupusPRO is a SLE specific patient reported outcomes measure developed and validated in the USA. This study aimed to validate the Hindi version of LupusPRO in systemic lupus erythematosus (SLE) patients in India. Methods: Disease activity and damage were assessed using SELENA–SLEDAI and SLICC/ACR damage Index respectively. Demographic and clinical features were recorded. The Hindi Version of LupusPRO and 36-Item Short Form Health Survey (SF-36) were administered for assessment of quality of life. Depression, anxiety and fatigue were assessed using Patient Health Questionnaire 9 (PHQ9), Generalized Anxiety Disorder 7 (GAD7) and Fatigue Severity Scale (FSS) respectively. Internal consistency reliability, test-retest reliability, convergent and discriminant validity (against corresponding domains of the SF-36, fatigue, depression and anxiety), criterion validity (against disease activity and damage) and known group validity were tested. Results: A total of 144 (140 females) patients with SLE with a mean age of 32.48 ± 7.26 years participated in the study. The median (interquartile range) SELENA SLEDAI was 2 (5.5). The internal consistency reliability of the LupusPRO domains was >0.7 for most domains (except for lupus symptoms, lupus medication, procreation and social support).We noted good convergent validity of LupusPRO domains with corresponding domains of SF-36, pain vitality with fatigue (FSS) and emotional health domain with depression (PHQ9) and anxiety (GAD7). Criterion validity of lupus symptoms with disease activity was observed. Known group validity of the LupusPRO domains with patient reported health status was observed. Confirmatory factor analysis showed a good fit. Conclusion: The Hindi LupusPRO has fair psychometric properties among Indian patients with SLE.